Assessing the financial and environmental impacts of precision irrigation in a humid climate - El Chami, D.; Knox, Jerry W.; Daccache, Andre; Weatherhead, E. K. (Czech Academy of Agricultural Sciences, 2019)
Precision agriculture is increasingly used where in-field spatial variability exists; however, the benefits of its use in humid climates are less apparent. This paper reports on a cost-benefit assessment of precision irrigation with variable rate technique (VRI) versus conventional irrigation, both compared to rainfed production, using a travelling hose-reel irrigator fitted with a boom on onions in eastern England. Selected environmental outcomes including water savings and CO2e emissions are evaluated. The modelled precision irrigation system, which responds to soil variability, generates better environmental outcomes than the conventional system in terms of water savings and reduced CO2e emissions (22.6% and 23.0% lower, respectively). There is also an increase in the ‘added value’ of the irrigation water used (£3.02/m3 versus £2.36/m3). Although precision irrigation leads to significant financial benefits from water and energy savings, these alone do not justify the additional equipment investment costs. However, any changes in yield or quality benefits, equipment costs or greater soil variability than on this site would make investment in precision irrigation more viable.
Keywords: variable rate irrigation; spatial soil variability; environmental impact; cost-benefit analysis